Mergers and acquisition strategies of Tata Motors - Kumar, M. Ashok; Winai Wongsurawat; Neal, Mark W.; Do, Ba Khang; Asian Development Bank (Japanese Scholarship) (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Waves of Mergers & Acquisition have been a feature of corporate history for more than a century now. Every time there has been an increase in Mergers & Acquisition activity, two important questions have surfaced, i.e., whether is this the right time to do the deal and if so, how can one win and create Value in such a competitive market. Many companies have successfully restructured their businesses in the past and they have borne profits in proportion to the GDP. Now many of them are ideally placed for the acquisition mode. The key ingredients for creating value & growth {u2013} profitability above the cost of capital and large reserves of cash, both seem to have been achieved by Corporates in the recent past. In 2007, the world{u2019}s credit markets also increased the amount they are willing to lend at lower rates which in turn spurs the acquisition growth. Based on above fundamentals, we have analyzed the strategies adopted by India{u2019}s Tata Motors over their acquisition of Daewoo Commercial Vehicles in South Korea and Jaguar Land Rover from Ford Motors in the United Kingdom.
A Research submitted in partial fulfillment of the requirements for the degree of Masters in Business Administration (International Business)
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2008
Keywords: Tata Motors; Automobile industry and trade; Consolidation and merger of corporations